Effectiveness of Internal Chemical Indicator Strips for Class IV and V - Insan S.K. Syah; Sohadi Warya; Vidhya Rohinee A/P Murugan@ Gopal; Anis Khoirunisa (Indonesian Journal of Pharmaceutical Science and Technology, 2015)
Infections through contaminated medical equipments are a serious threat to any patient’s safety and could be dangerous this treatment or may lead to new illness. Sterilization process was a compulsory procedure to ensure sterility of medical equipments where chemical indicators were broadly used to monitor sterilization process. The purpose of this study is to determine the development of internal chemical indicators strips of class IV and V in the steam sterilization in order to obtain good and quality products. Internal chemical indicator strips were able to provide visual verification on products that had passed through the sterilization process, with colour change on the indicator. The stages in this research had also included microbial contamination test Laminar Air Flow (LAF), dosage formulations Sodium Chloride (NaCl) 0.9% infusion, application of internal chemical indicator strips in the moist heat sterilization process and evaluation of NaCl 0.9% infusion that includes sterility test. This study was carried comprising 7 variations of time with data that showed a positive reaction for both indicators with a change of colour after 121 °C of sterilization. Sterility test showed no microbial growth starting from the sterilization time of 10.5 minutes. This research had successfully concluded that internal chemical indicator strips class IV and V were effective on steam sterilization at 121 °C for 10.5 minutes and could be used to monitor the sterilization process. Keywords:Internal chemical indicators strips of class IV and V, NaCl 0.9% infusion, steam sterilization